2013
DOI: 10.1007/s00018-013-1350-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin in tissue regeneration: timely disassembly of the scaffold is necessary to complete the build

Abstract: Tissue injury initiates extracellular matrix molecule expression, including fibronectin production by local cells and fibronectin leakage from plasma. To benefit tissue regeneration, fibronectin promotes opsonization of tissue debris, migration, proliferation, and contraction of cells involved in the healing process, as well as angiogenesis. When regeneration proceeds, the fibronectin matrix is fully degraded. However, in a diseased environment, fibronectin clearance is often disturbed, allowing structural var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 137 publications
4
68
0
3
Order By: Relevance
“…FN promotes tissue regeneration in multiple ways. It is known to be involved in clearing the tissue debris at the site of injury and influences both cell proliferation and differentiation by serving as a scaffold for cell adhesion and migration (Stoffels et al, 2013). We observed that FN is expressed during zebrafish fin regeneration (Fig.…”
Section: Tnc Fn and Lam Show Distinct Expression Patterns During Finmentioning
confidence: 71%
“…FN promotes tissue regeneration in multiple ways. It is known to be involved in clearing the tissue debris at the site of injury and influences both cell proliferation and differentiation by serving as a scaffold for cell adhesion and migration (Stoffels et al, 2013). We observed that FN is expressed during zebrafish fin regeneration (Fig.…”
Section: Tnc Fn and Lam Show Distinct Expression Patterns During Finmentioning
confidence: 71%
“…Collagen IV, together with laminin, constitutes the basement membrane that surrounds blood vessels in vivo. In addition, fibronectin was abundantly detected in coculture systems and it is a known ECM component of developing microvessels, acting also as a scaffold for cell adhesion and migration 43,44 and playing a role in the elongation of microvessels. 45 All these ECM components were secreted by HDF, providing the support for capillary-like structures formation.…”
Section: Ecm Production By the Different Cellsmentioning
confidence: 99%
“…Currently, the interaction between collagen or fibronectin and cartilage regeneration has drawn much attention (Aigner and Stöve, 2003;Stoffels et al, 2013). However, few review papers about potential roles of laminin and its isoforms on cartilage-forming cells for cartilage regeneration are available.…”
Section: Introductionmentioning
confidence: 99%